Adivasi art and activism : curation in a nationalist age - Tilche, Alice (Global South Asia., 2022)
"As India consolidates an aggressive model of economic development, indigenous tribal people known as adivasis continue to be overrepresented among the country's poor. Adivasis make up more than eight hundred communities in India, with a total population of more than 100 million people who speak more than three hundred different languages. Although their historical presence is acknowledged by the state and they are lauded as a part of India's ethnic identity today, their poverty has been compounded by the suppression of their cultural heritage and lifestyle. In Adivasi Art and Activism, Alice Tilche draws on anthropological fieldwork conducted in rural western India to chart changes in adivasi aesthetics, home life, attire, food, and ideas of religiosity that have emerged from negotiation with the homogenizing forces of Hinduization, development, and globalization in the twenty-first century. She documents curatorial projects located not only in museums and art institutions, but in the realms of the home, the body, and the landscape. Adivasi Art and Activism raises vital questions about preservation and curation of indigenous material and provides an astute critique of the aesthetics and politics of Hindu nationalism"--